Associations of Odonata with vegetation structure in different agricultural landscape - Ismail, Megat Naqiuddin Lutfie (2018)
Natural forest conversion into agricultural landscapes caused negative impacts on overall biodiversity. Agriculture landscapes, however, may have different impacts on biodiversity due to landscape heterogeneity. The present study investigated the abundance and species richness of dragonflies and damselflies (Insecta: Odonata) between monoculture and polyculture plantations. Three different agricultural landscape namely; oil palm and rubber for monoculture plantations and orchard for polyculture plantations were assessed for Odonata communities in Kampung Sungai Lalah, Pedas, Negeri Sembilan. Orchard, oil palm and rubber plantation visited in this study shared the same water source, Sungai Lalah, which makes it convenient to compare Odonata composition. Odonata sampling was conducted using visual observations in 15 sampling points that have close proximity to river in each agricultural landscapes (total 45 sampling points). We encountered 797 individuals belonging to 20 species and 5 families of Odonata. Orchard had the greatest Odonata abundance (51%) and species richness (44%) followed by oil palm and rubber plantations. Polyculture practise in orchard showed significantly greater vegetation cover, relative humidity and temperature that are more favoured by Odonata. The findings indicate that polyculture practices in orchard provide more intricate resources due to greater habitat heterogeneity. Variety of vegetation cover can serve as food resources and habitats for Odonata. In conclusion, polyculture landscape can sustain diverse Odonata communities compared to monoculture landscape. Therefore, it is important to conserve and manage agricultural landscapes towards polyculture practise for Odonata species conservation.